Russia and the Golden Horde : The Mongol Impact on Medieval Russian History - Halperin, Charles J. (Book collections on Project MUSE., 1985)
" ... An imaginative and dispassionate re-examination of the significance of the Mongol Conquest and its aftermath for Russia's historical development."--Slavic Review"On all counts Russia and the Golden Horde infuses the subject with fresh insights and interpretations." -History"Combining rigorous analysis of the major scholarly findings with his own research, Halperin has produced both a much-needed synthesis and an important original work." -Library Journal"Halperin's new book combines sound scholarship and a flair for storytelling that should help publicize this all too unfamiliar tale in the West." -Virginia Quarterly Review"It is a seminal work that will be repeatedly cited in the future ..." -The Historian" ... ingenious and highly articulate ..." -Russian Review